Предмет: Алгебра, автор: sf2018

779 срочно, спасибо.

Приложения:

Ответы

Автор ответа: Universalka
1

1)Ctg\alpha*Sin(-\alpha )-Cos(-\alpha)=-\frac{Cos\alpha}{Sin\alpha}*Sin\alpha-Cos\alpha=-Cos\alpha-Cos\alpha=-2Cos\alpha\\\\Otvet:\boxed{-2Cos\alpha}

2)\frac{1-Sin^{2}(-x) }{Cosx}=\frac{1-Sin^{2}x}{Cosx}=\frac{Cos^{2}x }{Cosx}=Cosx\\\\Otvet:\boxed{Cosx}

3)tg(-\beta )*Ctg\beta+Sin^{2}\beta=-tg\beta*Ctg\beta+Sin^{2}\beta=-1+Sin^{2}\beta=-(1-Sin^{2}\beta)=-Cos^{2}\beta\\\\Otvet:\boxed{-Cos^{2}\beta}

4)\frac{tg(-x)+1}{1-Ctgx}=\frac{1-tgx}{1-Ctgx}=\frac{1-tgx}{1-\frac{1}{tgx}}=\frac{1-tgx}{\frac{tgx-1}{tgx} } =\frac{(1-tgx)*tgx}{tgx-1}=-tgx\\\\Otvet:\boxed{-tgx}

Похожие вопросы
Предмет: Геометрия, автор: alexbratishka2200